Transmission Control Protocol (TCP)-Based Delay Tolerant Networking for Space-Vehicle Communications in Cislunar Domain: An Experimental Approach - Ding Wang; Ruhai Wang (Sensors)
The integrated heterogeneous 7G/8G networks may face multiple challenges for reliable data delivery such as link disruption, intermittent link availability, long latency and a highly lossy channel. Delay tolerant networking (DTN) was proposed as a highly reliable networking technology for space networks that will be part of future 7G/8G networks. In this paper, an experimental evaluation of transmission control protocol (TCP)-based DTN (i.e., running TCP at the transport layer of DTN) for space-vehicle communications in the cislunar domain is presented. The impact of link disruption is also considered. The evaluation was conducted using the DTN protocol suites over a realistic experimental testbed. The study results show that TCP-based DTN works effectively for space-vehicle communications in cislunar domain in the presence of a link disruption event. However, a roughly exponential goodput decrease is observed with a linear increase in link delay from 1250 ms to 5 s.